Integration of AI and OR Techniques in Constraint Programming for Combinatorial Optimization Problems 5th International Conference, CPAIOR 2008 Paris, France, May 20-23, 2008 Proceedings - Perron, Laurent; Trick, Michael A. (Theoretical Computer Science and General Issues, 2008)
The 5th International Conference on Integration of AI and OR Techniques in Constraint Programming for Combinatorial Optimization Problems (CPAIOR 2008) was held in Paris, France May 20-23, 2008. The purpose of this conference series is to bring together researchers in the ?elds of constraint programming, arti?cial intelligence, and operations research to explore ways of solving large-scale, practical optimization problems through integration and hybridization of the ?elds' di?erent techniques. Through the years, this research community is discovering that the ?elds have much in c- mon, and there has been tremendous richness in the resulting cross-fertilization of ?elds. This year, we allowed submissions of both long (15 page) and short (5 page) papers, with short papers either being original work, a reduced version of a long paper, or an extended abstract of work published elsewhere. We were not s- prised by the 69 submissions in the long paper category: this is an active ?eld with many researchers. We were surprised by the 61 short paper submissions. This was far more than predicted. With 130 high-quality submissions, compe- tion for acceptance in this year's program was particularly ?erce. In the end, we accepted 18 long papers and 22 short papers for presentation and publication in this volume.